Upregulation of mir-1199-5p is associated with reduced type 2 5-α reductase expression in benign prostatic hyperplasia - Zhanliang Liu; Zhemin Lin; Fang Cao; Mingxin Jiang; Song jin; Yun Cui; YN Niu (BMC Urology, 2022)
Abstract Background 5-α reductase inhibitors (5-ARIs) are first-line drugs for managing benign prostatic hyperplasia (BPH). Unfortunately, some patients do not respond to 5-ARI therapy and may even show worsening symptoms. The decreased expression of steroid 5-α reductase type 2(SRD5A2) in BPH tissues may explain the failure of 5-ARI therapy, however, the mechanisms underlying SRD5A2 decreased remained unelucidated. Objectives To investigate microRNA-mediated regulation of the expression of SRD5A2 resulting in 5-ARI therapy failure. Materials and methods The expression of SRD5A2 and microRNAs in BPH tissues and prostate cells were detected by immunohistochemistry, western blotting, and quantitative real-time PCR. Dual-luciferase reporter assay was performed to confirm that microRNA directly combine to SRD5A2 mRNA. The apoptosis of prostatic cells was detected by flow cytometry. Results SRD5A2 expression was variable; it was negative, weak, and strong in 13.6%, 28.8%, and 57.6% of BPH tissues respectively. The normal human prostatic epithelial cell line RWPE-1 strongly expressed SRD5A2, whereas the immortalized human prostatic epithelial cell line BPH-1 weakly expressed SRD5A2. miR-1199-5p expression was remarkably higher in BPH-1 than in RWPE-1 cells(P<0.001), and miR-1199-5p expression was significantly upregulated in BPH tissues with negative SRD5A2 expression than those with positive SRD5A2 expression. Transfection of miR-1199-5p mimics in RWPE-1 cells led to a marked decrease in SRD5A2 expression, whereas miR-1199-5p inhibitor increased SRD5A2 expression in BPH-1 cells. Dual-luciferase reporter assay showed that miR-1199-5p could bind the 3′untranslated region of SRD5A2 mRNA. miR-1199-5p also decreased the RWPE-1 sensibility to finasteride, an inhibitor of SRD5A2. Conclusion Our results show that SRD5A2 expression varies in BPH tissues and miR-1199-5p might be one of the several factors contributing to differential SRD5A2 expression in BPH patients.